Evaluación del desarrollo de la agricultura periurbana en el distrito de Cayma - Arequipa y propuesta de gestión integral con participación del Gobierno Local - Benavente Cardenas, Claudia Pilar (2018)
Peri-urban agriculture (PA) is a multifunctional activity that contributes to the developmentof inclusive and comprehensive policies, with social, economic and environmental benefits.The commercial opening represents threats and opportunities in the agricultural sector of theperi-urban zones of our country, making it vulnerable and a precarious and discouragedsector; in our context, it is considered small scale or rural and it is attributed the responsibilityof internal food security, for this reason it is necessary that this traditional agricultural sectorbecomes a more competitive, modern and sustainable sector.The present investigation had as objective: to determine the technical - productive capacity,the organizational structure and the external environment of the peri - urban agriculturalactivity in the period July 2016 - May 2017 and to propose a proposal of management ofagricultural development with the local government (GL) . The research was descriptive -analytical, with a qualitative approach, using the action research method of the participatorytype and is based on the methodological guide proposed by FAO (2016); the informationcollection instruments that were used were: surveys, participant observation, problem tree,SWOT analysis (strengths-opportunities-weaknesses-threats) and focus groups.The study began with the diagnosis of the productive, environmental, political and socialenvironment; allowing to establish real causes of the current problem, existing potentialitiesand the relationship and interaction with the other factors of the environment of the activity.The results indicate that 43.5% of farmers are engaged in other economic activities and40.7% have less than one hectare, perceiving it as a secondary source of income; Thechallenges presented by the PA are related to the absence of specific public policies, lack ofcurrent information, scarce citizen participation, scarce public and private intervention in theperi-urban agricultural sector; then, the vision was developed participatively with thechanges that are intended to be achieved, strategies of integral development were formulatedthat have as components: the organizational, productive - technological, environmental -natural and nutritional resources and food hygiene. Finally, it is proposed that thedevelopment of agriculture in the Cayma district be based on co-management betweenfarmers and authorities for their integral development